Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien pada Puskesmas Tanjungsari di Gunungkidul, Daerah Istimewa Yogyakarta - Saputra, Dimas Mastra Dewa; Partina, Anna; Amallia, Bunga Alfausta (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
Health services are one of the basic needs that must be met to improve the quality of life of the community. Patient satisfaction is the main factor that determines the quality of health services such as Community Health Centers. The purpose of this study was to study the effect of service quality on patient satisfaction. This study uses the SERVQUAL Model used as an approach in measuring service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study uses a quantitative method with a survey technique through a questionnaire distributed to outpatients of the Tanjungsari Community Health Center. The research sample consisted of 100 respondents selected using the purposive sampling method. Data analysis was carried out using multiple linear regression analysis. The results showed that tangentiality did not have a significant effect on patient satisfaction. Trust, responsiveness, confidence, and empathy had a positive and significant effect. Simultaneously, patient satisfaction at the Tanjungsari Community Health Center was influenced by the five dimensions of service quality. As a result, community health centers must improve service quality through more responsive interactions, increasing patient trust, and a more empathetic approach to providing health services.